Restorative justice : theories and practices of moral imagination - Levad, Amy, 1979- (Criminal justice (LFB Scholarly Publishing LLC), 2012)
Levad explores the?moral imagination? of restorative justice as an alternative framework for understanding and responding to crime, drawing together philosophical virtue ethics inspired by Aristotle?s discussion of equity as the highest form of justice?a form of justice that requires vivid and expansive moral imagining?and an ethnography of restorative justice programs. Levad maintains that because participants in restorative justice practices become adept at vivid and expansive moral imagining, they are better able to realize justice and equity in response to particular cases. She concludes.